PENGARUH KECERDASAN ADVERSITY, PERTIMBANGAN PASAR KERJA DAN PERSEPSI MENGENAI PROFESI AKUNTAN PUBLIK TERHADAP MINAT MENJADI AKUNTAN PUBLIK - Ni Made Emi Hudiyani; Ni Putu Ayu Kusumawati; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2020)
The interest inbecoming a public accountant is an individual's interest in the public accountingprofession. Public Accountants have an important role insupporting increased transparency andquality of financial information. Public interest in becoming a public accountant is relatively low.The purpose of this study was to determine the effect of adversity intelligence, labor marketconsiderations, and perceptions about the profession of public accountants on the interest of beinga public accountant. This research was conducted on 2017 accounting student at the Faculty ofBusiness Economics and Tourism, Hindu University of Indonesia, Denpasar. The number ofsamples taken was 189 people, with non-probability sampling method with purposive samplingtechnique. Data collection was carried out using a questionnaire. The analysis data techniqueused is multiple linear regression.The results showed that adversityintelligence, labor marketconsiderations, and perceptions about the public accounting profession had positive effect oninterest of accounting students at the HinduUniversity of Indonesia to become a public accountant.